Potensi Karbon dan Nilai Jasa Lingkungan di Agroforestri LPHN (Lembaga Pengelola Hutan Nagari) Sungai Buluh, Padang Pariaman, Sumatera Barat - Lily Rahmawati; Chairul; Solfiyeni (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze biomass quantity, carbon reserves, carbon sequestration, and to determine the environmental value of carbon sequestration in the agroforestry area of LPHN Sungai Buluh Padang Pariaman. This is because agroforestry areas can also play a role in carbon sequestration in addition to their economic function for the community. This study was conducted using purposive sampling to determine the location of 30 observation plots. Data collection was carried out using destructive sampling for undergrowth and litter data and non-destructive sampling for tree and sapling strata data. The results of this study were a total biomass of 280.768 tons/ha, total carbon reserves obtained from the biomass value of 131.955 tons/ha, and total carbon sequestration of 484.294 tons/ha. Meanwhile, the environmental service value of carbon sequestration was IDR 82,566,423,881.28/ton/year. The environmental service value obtained from this research location is relatively low compared to studies conducted in other locations, primarily due to the limited vegetation types and small study area.